A study of the degradation of marine concrete under the coupled effect of wetting–drying cycles and bending loads. (May 2015) - Liu, J.; Deng, J.; Qin, H.; Zhang, P.; Pang, C.; Sun, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Marine concrete with excellent salt corrosion resistance was cast, followed by ultrasonic testing technology, chemical analysis of free chloride ion and calculation of the chloride ion diffusion coefficient to investigate the degradation of the marine concretes subjected to wetting–drying cycles and bending loads during their exposure to a marine environment. Additionally, an indoor accelerated corrosion test was conducted. The effects of the water-to-binder ratio, mineral admixtures, bending loads and other factors on the durability of the marine concrete were investigated, and initial primary correlation between marine exposure conditions and the indoor accelerated corrosion test was established based on the diffusion coefficient of chloride ions.